"He put to the sword all his brothers" (2Chr 21,4)? - Abecassis, Ilan (2015)
In Chronik 2 lesen wir, dass Joram, Sohn von Joschafat, „alle seine Brüder töten lässt“. Einige Faktoren entschärfen dieses Bild: Das Fehlen einer entsprechenden Referenz im Buch der Könige, fünf Massaker von judäischen Prinzen werden in der Generation von Joram beschrieben, der Gebrauch von literarischen Elementen, Brudermord war eine persische Tradition und der Gebrauch von allgemeinen Aus-drücken. Es muss daher dieses Bild als reine Erfindung gelten.
Although 2 Chronicles records that Jehoram son of Jehoshaphat “put to the sword all his brothers,” several factors mitigate against understanding this statement literally: the lack of reference to the event in Kings, the fact that five massacres of Judean princes are said to have occurred during Jehoram’s generation, the use of literary elements, the knowledge that fratricide was a Persian custom, and the use of general expressions. It must therefore be regarded as a fictional account.
Keywords: Bibel